1988
DOI: 10.1530/jrf.0.0840037
|View full text |Cite
|
Sign up to set email alerts
|

Conceptus development in Large White and prolific Chinese Meishan pigs

Abstract: Large White (LW) and Meishan (MS) gilts were killed on Days 8, 10, 11, 12, 14 and 30 of gestation. Mean diameters (mm) for MS and LW conceptuses, respectively, were: Day 8, 0.45 and 0.69; Day 10, 2.7 and 1.9; Day 11, 5.3 and 2.7, with the differences among days being affected by breed (P less than 0.01). Variation in diameter among conceptuses from LW gilts was greater (P less than 0.01) than that for MS gilts on Days 8-11, respectively: Day 8, 20 and 46%; Day 10, 29 and 38%; and Day 11, 22 and 44%. Conceptuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
80
2
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(92 citation statements)
references
References 6 publications
7
80
2
3
Order By: Relevance
“…In common with the genetic study of Haley and Lee (1990) (Wrathall, 1971; present study) and after adjustment to a common ovulation rate, the difference in favour of the Meishan would therefore be about 0.3 in the study of Bazer et al (1988) and 0.15 in the study . Given The relationship between uterine capacity and uterine size is uncertain, and in fact this study confirms that of Bazer et al (1988) (Bidanel et al, 1990b;Haley and Lee, 1990 or in piglet weight (Bidanel et al, 1990b;Haley et al, 1992 (Bidanel et al, 1989;Haley and Lee, 1990). In the study of Haley and Lee (1990) …”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…In common with the genetic study of Haley and Lee (1990) (Wrathall, 1971; present study) and after adjustment to a common ovulation rate, the difference in favour of the Meishan would therefore be about 0.3 in the study of Bazer et al (1988) and 0.15 in the study . Given The relationship between uterine capacity and uterine size is uncertain, and in fact this study confirms that of Bazer et al (1988) (Bidanel et al, 1990b;Haley and Lee, 1990 or in piglet weight (Bidanel et al, 1990b;Haley et al, 1992 (Bidanel et al, 1989;Haley and Lee, 1990). In the study of Haley and Lee (1990) …”
Section: Introductionsupporting
confidence: 63%
“…In both France (Bidanel et al, 1989) and the UK (Haley and Lee, 1990) (Bolet et al, 1986;Bazer et al, 1988;Bidanel et al, 1990a), whereas studies on the UK Meishan sample have found signifi¬ cantly higher ovulation rates in both gilts and sows than in Large White females Haley and Lee, 1990;Wilmut et al, 1992). With no advantage to the Meishan in ovulation rate, the prolificacy of the French sample compared with the Large White breed is due to enhanced pre¬ natal survival (Bolet et al, 1986;Bazer et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Puberty occurs at about 3 months, thus much earlier than in European pig breeds (6-7 months). Average litter sizes are 30-40% higher than those of contemporary Large White pigs (Bolet et al, 1986; (Bidanel and Legault, 1986;Bazer et al, 1988; On day 20 of lactation, blood samples (3 ml) were taken for 6 h at 15-min intervals for analysis of LH. On day 22 all sows received an im injection of 15 5 og oestradiol benzoate (OB, Progynon B Oleosum, Schering)/kg body weight.…”
mentioning
confidence: 99%
“…All sows were inseminated or mated at least twice during induced oestrus. Pregnancy was tested by echography 4 weeks after insemination or mating (Martinat-Botté et al, 1988).…”
mentioning
confidence: 99%